Animal tracks and human footprints in prehistoric hunter-gatherer rock art of the Doro! nawas mountains (Namibia), analysed by present-day indigenous tracking experts - Lenssen-Erz, Tilman; Pastoors, Andreas; Uthmeier, Thorsten; Ciqae, Tsamgao; Kxunta, Ui; Thao, Thui (PLoS ONE, 2023)
Namibia is rich in hunter-gatherer rock art from the Later Stone Age (LSA); this is a tradition of which well-executed engravings of animal tracks in large numbers are characteristic. Research into rock art usually groups these motifs together with geometric signs; at best, therefore, it may provide summary lists of them. To date, the field has completely disregarded the fact that tracks and trackways are a rich medium of information for hunter-gatherers, alongside their deeper, culture-specific connotations. A recent research project, from which this article has emerged, has attempted to fill this research gap; it entailed indigenous tracking experts from the Kalahari analysing engraved animal tracks and human footprints in a rock art region in central Western Namibia, the Doro! nawas Mountains, which is the site of recently discovered rock art. The experts were able to define the species, sex, age group and exact leg of the specific animal or human depicted in more than 90% of the engravings they analysed (N = 513). Their work further demonstrates that the variety of fauna is much richer in engraved tracks than in depictions of animals in the same engraving tradition. The analyses reveal patterns that evidently arise from culturally determined preferences. The study represents further confirmation that indigenous knowledge, with its profound insights into a range of particular fields, has the capacity to considerably advance archaeological research.
CRIS-Team Scopus Importer:2023-09-29

ArtefactViewer-a 3D tool for archeologists - Pastoors, Andreas; Wickeroth, Daniel; Laurentius, Dominic; Lang, Ulrich (2015)

Cave art in context: Methods for the analysis of spatial organization in cave sites - Pastoors, Andreas; Weniger, Gerd-Christian; et al. (Journal of Archaeological Research, 2011)

Convergent evidence of eagle talons used by late Neanderthals in Europe: a further assessment on sybolism - Romandini, Matteo; Peresani, Marco; Laroulandie, Véronique; Metz, Laure; Pastoors, Andreas; Vaquero, Manuel; Slimak, Ludovic (PLoS ONE, 2014)

Cultural contact over the Strait of Gibraltar during the middle palaeolithic? Evaluating the visibility of cultural exchange - Tafelmaier, Yvonne; Pastoors, Andreas; Weniger, Gerd-Christian (Munibe Antropologia-Arkeologia, 2017)
Possible contacts between hunter-gatherers of Northern Africa and Europe via the Strait of Gibraltar during the Pleistocene are still object to discussions. In the absence of significant fossil remains, debates are mainly based on similarities and differences of singular aspects of material culture. However, a theoretical framework for these discussions was lacking. The first aim of this study thus has been the development of a theoretical base. We therein included Maslow´s pyramid of basic needs. The idea of our approach is that the presence or absence of so-called cultural tracers identify either contact or disparity. A large database on archaeological sites of Morocco and Southern Iberia dating between 160 ka and 40 ka years ago has been compiled, containing information about lithic technology and typology, lithic raw material acquisition, subsistence patterns and symbolic behaviour. We formulated three potential contact scenarios between the two regions. The presence and/ or absence of so-called cultural tracers within the data set, that covered all levels of Maslow´s pyramid, led us to conclude that – based on the present archaeological and anthropological data - no contact took place between Iberian and North African populations across the Strait of Gibraltar in the given time frame.
Created from Fastlane, Scopus look-up
Keywords: Corridor; Cultural transmission; Mousterian; Neanderthal

Die mittelpaläolithische Freilandstation von Salzgitter-Lebenstedt. Genese der Fundstelle und Systematik der Steinbearbeitung - Pastoors, Andreas (Ruth Printmedien, 2001)

Die Schäl Sick kommt. Zwei paläolithische Steinartefakte im Kölner Stadtgebiet aus Dellbrück und Eil (Nordrhein-Westfalen, Deutschland) - Pastoors, Andreas (Stone Age. Studying Technologies Of Non-analogous Environments And Glacial Ecosystems, 2024)

Engravings in the upper rock shelter of Abri Allerberg (Lower Saxony). Evaluation authenticity of possible Late Glacial or early Holocene rock art in northern Germany - Grote, Klaus; Pastoors, Andreas; Binnie, Ariane; Blumenröther, Julia; Hallmann, Christoph; Hoffmeister, Dirk; Hoppert, Michael; Lehmann, Jens; Lenssen-Erz, Tilmann; Maier, Andreas; Siegesmund, S; Terberger, Thomas; et al. (Palaeolithic rock and cave art in Central Europe? Proceedings of the XIXe International Rock Art Conference „Symbols in the landscape. Rock art and its context“ in Cáceres, 2015, 2019)

Enlène et les Trois-Frères - Pastoors, Andreas; Bégouën, Robert; Feruglio, Valérie (Bouquetins et Pyrénées: Inventaire des représentatioins du Paléolithique pyrénéen, 2022)

Enlène et les Trois-Frères, grottes (Montesquieu-Avantès, Ariège, France) - Pastoors, Andreas; Feruglio, Valérie; Bégouën, Robert (2021)

Episodes of magdalenian hunter-gatherers in the upper gallery of tuc d'audoubert (Ariege, France) - Pastoors, Andreas; Lenssen-Erz, Tilman; Ciqae, Tsamgao; Kxunta, /Ui; Thao, Thui; Bégouën, Robert; Uthmeier, Thorsten (Springer International Publishing, 2021)
The Tuc d'Audoubert cave (Ariege, France) offers unique insights into the life of Late Pleistocene hunters-gatherers due to its exceptionally good preservation conditions. This is especially true for the 300 footprints in the upper gallery of the cave. Even for the layperson, some trackways are easily recognized. Short episodes of past life become tangible. The spectrum of scientific analytic methods used in western science has not yet provided an option to interpret these visible episodes satisfactorily. For this reason, tracking experts, i.e. indigenous ichnologists, were invited to analyse the footprints in Tuc d'Audoubert. With their dynamic approach of identification, they are able to do justice to the dynamics embodied in the footprints. In total, eight main concentrations in four different locations were studied. Two hundred fifty-five footprints were identified and grouped into 24 events. In view of the group compositions and the assumption that humans did not climb alone into the upper gallery for security reasons, it can be concluded that a maximum of five visits by two to six subjects were carried out. Among the events, the couple of an adult man and an adult woman, who appear together in a total of ten different spots, is particularly noteworthy. Altogether, this study is a first step of a multi-stage procedure. Further analyses based on measurements and plantar pressure analyses will follow.
Created from Fastlane, Scopus look-up
Keywords: Event identification; Footprints; Upper Palaeolithic

Excavations in Solutrean Levels of Ardales Cave (Málaga) - Pastoors, Andreas; Ramos-Munoz, Jose (Human Adaptationsj to the Last Glacial Maximum: The Solutrean and its Neighbors, 2019)

Experience based reading of Pleistocene human footprints in Pech-Merle - Pastoors, Andreas; Lenssen-Erz, Tilman; Breuckmann, Bernd; Ciqae, Tsamkxao; Kxunta, Ui; Rieke-Zapp, Dirk; Thao, Thui (Quaternary international, 2017)

Fährtenleser blicken 17000 Jahre in die Vergangenheit - Pastoors, Andreas; Lenssen-Erz, Tilman (Archäologie in Deutschland, 2015)

Flakes not blades. The role of flake production at the onset of the Upper Palaeolithic in Europe - Pastoors, Andreas; Peresani, Marco (2012)

Höhlenkunst und Raum: Archäologische und architektonische Perspektiven - Pastoors, Andreas; Weniger, Gerd-Christian (Jan van der Most, 2003)

Introduction - Pastoors, Andreas; Lenssen-Erz, Tilmann (Reading Prehistoric Human Tracks, 2021)
This book explains that after long periods of prehistoric research in which the importance of the archaeological as well as the natural context of rock art has been constantly underestimated, research has now begun to take this context into focus for documentation, analysis, interpretation and understanding. Human footprints are prominent among the long-time under-researched features of the context in caves with rock art. In order to compensate for this neglect an innovative research program has been established several years ago that focuses on the merging of indigenous knowledge and western archaeological science for the benefit of both sides. The book composes first the methodological diversity in the analysis of human tracks. Here major representatives of anthropological, statistical and traditional approaches feature the multi-layered methods available for the analysis of human tracks. It second compiles case studies from around the globe of prehistoric human. For the first time the most important sites which have been found worldwide are published in a single publication. The third focus of this book is on first hand experiences of researchers with indigenous tracking experts from around the globe, expounding on how archaeological science can benefit from the ancestral knowledge.<br

Kultraum oder Bilderhöhle? Über den Kontext prähistorischer Felsbilder - Pastoors, Andreas (Kulträume: Studien zum Verhältnis von Kult und Raum in alten Kulturen, 2017)

L’Abri du Rhinocéros à Montesquieu-Avantès (France) - Bégouën, Robert; Berke, Hubert; Pastoors, Andreas (Bulletin de la Société Préhistorique de l'Ariège, 2013)

La caverne des Trois-Frères. Anthologie d'un exceptionnel sanctuaire préhistorique - Bégouën, Robert; Clottes, Jean; Feruglio, Valérie; Pastoors, Andreas (2014)

La grotte d’Enlène. Immersion dans un habitat magdalénien - Pastoors, Andreas; Clottes, Jean; Bégouën, Robert (In Fine éditions d’art, 2019)

Last Neanderthal occupations at Central Iberia: the lithic industry of Jarama VI rock shelter (Valdesotos, Guadalajara, Spain) - Ruiz, Marta Navazo; Jordá Pardo, Jesús F.; Burow, Christoph; Kehl, Martin; Pastoors, Andreas; Weniger, Gerd Christian; Wood, Rachel (Archaeological and Anthropological Sciences, 2020)
The work undertaken at the Jarama VI site (Valdesotos, Guadalajara, Spain) in the 1990s resulted in the recovery of thousands of archeological remains from the three Pleistocene sedimentary units of this cavity. Prior to the systematic analysis of the lithic material and the reception of new geochronological data, it had been suggested that the upper unit of Jarama VI could correspond to the Early Upper Paleolithic, while the other two units could be related to Neanderthal occupations. We now present the results of a comprehensive analysis and review of the materials, enabling us to clarify that all three units at Jarama VI belong to the Middle Paleolithic and, hence, to the last known Neanderthals in this central area of the Iberian Peninsula, a relatively high altitude inland zone within the framework of mountainous landscapes—parameters which seem to be characteristic of these last groups of Neanderthals.
Created from Fastlane, Scopus look-up
Keywords: Central Iberia; Lithic industry; Middle Paleolithic; Neanderthals; Technology

Les altérations modernes des peintures de Pech-Merle - Pastoors, Andreas; Bourges, François; Lartiges, Bruno; Genty, Dominique; Perrier, Frédéric (Préhistoire ariégeoise, 2022)

Le sanctuaire secret des bisons. Il y a 14 000 ans dans la caverne du Tuc d’Audoubert … - Pastoors, Andreas; Bégouën, Robert; Fritz, Carole; Tosello, Gilles; Clottes, Jean; Faist, François (Somogy, 2009)

Les bouquetins d’Enlène et des Trois-Frères (Ariège, France) - Pastoors, Andreas; Feruglio, Valérie; Bégouën, Robert (Bouquetins et Pyrénées: De la Préhistoire à nos jours, 2021)

Loess formation and chronology at the Palaeolithic key site Rheindahlen, Lower Rhine Embayment, Germany - Kehl, Martin; Seeger, Katharina; Pötter, Stephan; Schulte, Philipp; Klasen, Nicole; Zickel, Mirijam; Pastoors, Andreas; Claßen, Erich (E&G Quaternary science journal, 2024)
The loess–palaeosol sequence and intercalated Palaeolithic find layers at the former brickyard of Rheindahlen are matters of ongoing scientific dispute. The age of different palaeosols and loess layers, hence their correlation with the global climate cycles, and the timing of repeated Neanderthal occupations have been hotly debated. These disagreements should be solved because the exceptional sedimentary and Palaeolithic sequences at Rheindahlen provide a unique opportunity to study diachronic changes in Neanderthal behaviour within the context of past climate change. We thus revisited one of the key loess sections of the Rheindahlen site to improve our understanding of loess formation processes and provide a more reliable chronostratigraphic framework for the sequence. High-resolution grain size analyses and micromorphology show that the Erkelenz Soil and the Rheindahlen Soil are characterized by more strongly developed Bt horizons than the modern soil. While these soils represent interglacial phases, the lowermost palaeosol likely formed during an interstadial and has been overprinted by weak clay illuviation during the formation of the Rheindahlen Soil. Sedimentary features of prolonged frost characterize loess and palaeosols below the modern soil and give indirect evidence for a Holocene age of the uppermost part of the sequence. Our luminescence dating approach corroborates this correlation and adds several Last Glacial deposition ages for the upper metres of the sequence. Previous correlation of this part of the sedimentary sequence with the penultimate glacial is thus rejected, whereas placing the Middle Palaeolithic inventories A3, B1, and B2 into the Last Glacial is confirmed. Luminescence measurements for the parental loess of the Erkelenz Soil and for loess layers below did not provide reliable ages probably related to signal saturation. The age of this part of the sequence thus remains open, hence the timing of human occupation testified by Palaeolithic inventories B3, B4/5, C1, and D1. The new findings provide an improved base for stratigraphic correlation of the Rheindahlen loess sequence and for investigating diachronic change in Neanderthal behaviour against the background of past climate change.<br
CRIS-Team Scopus Importer:2024-02-16

Mit dem Rücken zur Kunst. Der Kontext eiszeitlicher Höhlenbilder - Pastoors, Andreas (2016)

New light on the Middle Palaeolithic quartzite extraction site Troisdorf-Ravensberg - Pastoors, Andreas; Kehl, Martin; Prieto, Alejandro; Henselowski, Felix; King, Georgina; Peresani, Marco; Vaquero, Manuel; Claßen, Erich (Bonner Jahrbücher des LVR-Landesmuseums Bonn, 2022)

Palaeolithic rock and cave art in Central Europe? - Pastoors, Andreas; Floss, Harald (Marie Leidorf, 2018)

Paläolithische Kunst in Bayern - Pastoors, Andreas (Steinzeit in Bayern, 2023)

Petrological characterisation of the “Tertiary quartzites” from the site of Troisdorf-Ravensberg (North Rhine-Westphalia, Germany): first insights in Middle Palaeolithic outcrop exploitation - Pastoors, Andreas; Prieto, Alejandro; Yusta, Iñaki; Claßen, Erich (Quartär : internationales Jahrbuch zur Eiszeitalter- und Steinzeitforschung, 2020)

Petrological characterisation of the “Tertiary quartzites” from the site of Troisdorf-Ravensberg (North Rhine-Westphalia, Germany): first insights in Middle Palaeolithic outcrop exploitation Petrologische Charakterisierung der „tertiären Quarzite“von Troisdorf-Ravensberg (Nordrhein-Westfalen, Deutschland): Erste Einblicke in die Nutzung des mittelpaläolithischen Aufschlusses - Prieto, Alejandro; Yusta, Iñaki; Pastoors, Andreas; Claßen, Erich (Hugo Obermaier-Society for Quaternary Research and Archaeology of the Stone Age, 2019)
The new excavations carried out at the site of Troisdorf-Ravensberg in 2015 have brought to light an essential part of Neanderthal daily life: the procurement mechanism of lithic raw material. The first hypothesis to understand this site propounds that it was used as a quartzite workshop or a quarry site where extractive and first knapping activities were performed in the Middle Palaeolithic. Against this background this study focusses on the petrological characterisation of the quartzites from Troisdorf-Ravensberg using a solid geoarchaeological protocol based on petrographic-stereomicroscopic petrology and geochemical composition. These procedures allowed us to characterise the “Tertiary quartzites” at this site and to establish two types and two varieties of this raw material based on the features which led us to understand the stone formative processes. The latter is related with sedimentary processes and the formation of silcretes. Preliminary data puts forward a selective extraction and exploitation of a specific facies, the secondary exploitation of a by-product type, and the discard of the last variety. This complex raw material exploitation is suggested by the technological markers observed, which connect the physical properties of the stone, based on silica cementation of the former quartz arenite, and the procurement strategies carried out by the Middle Palaeolithic people. The qualitative differences in the raw material are an important aspect of the anthropogenic selection that can be identified in the Troisdorf assemblage. Other selection criteria, especially the morphology of the raw pieces or technological requirements, certainly play also a major role, but are not part of this contribution.
CRIS-Team Scopus Importer:2024-12-16
Keywords: geoarchaeology; Middle Palaeolithic; petrography; raw material; silcrete; Wavelength Dispersive-X Ray Fluorescence

Pleistocene foragers on the Iberian Peninsula: Their culture and environment. Festschrift in honour of Gerd-Christian Weniger for his sixtieth birthday - Pastoors, Andreas; Auffermann, Bärbel (2013)

Pleistocene foragers: Their culture and environment. Festschrift in honour of Gerd-Christian Weniger for his sixtieth birthday - Pastoors, Andreas; Auffermann, Bärbel (2013)

Quantification of late Pleistocene core configurations: Application of the Working Stage Analysis as estimation method for technological behavioural efficiency - Pastoors, Andreas; Tafelmaier, Yvonne; Weniger, Gerd-Christian (Quartär : internationales Jahrbuch zur Eiszeitalter- und Steinzeitforschung, 2015)

Radiocarbon and U-series age constraints for the Lateglacial rock art of Sicily - Di Maida, G.; Mannino, M. A.; Zilhão, J.; Hoffmann, D. L.; García-Diez, M.; Pastoors, Andreas; Standish, C. D.; Pike, A. W.G.; Olsen, J.; Schimmenti, V.; Battaglia, G.; Terberger, T. (Quaternary Science Reviews, 2020)
The presence of rock and portable art on Sicily has been recognized since World War II. This record has been unanimously attributed to the Upper Palaeolithic in the published literature, based almost uniquely on stylistic reasoning. Here we present the first absolute dates in direct association with the Sicilian art record. These data provide new insights into the life of Southern European hunter-gatherers and their relationships with coeval groups from Western Europe, contributing a fresh perspective on the ongoing discussion about the development and co-existence of different art traditions in Europe during the final phases of the Pleistocene and at the beginning of the Holocene.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Addaura; Lateglacial; Portable art; Rock art; Sicily; Upper palaeolithic

Reading Prehistoric Human Tracks. Methods & Material - Pastoors, Andreas; Lenssen-Erz, Tilmann (Springer Nature, 2021)
This Open Access book explains that after long periods of prehistoric research in which the importance of the archaeological as well as the natural context of rock art has been constantly underestimated, research has now begun to take this context into focus for documentation, analysis, interpretation and understanding. Human footprints are prominent among the long-time under-researched features of the context in caves with rock art. In order to compensate for this neglect an innovative research program has been established several years ago that focuses on the merging of indigenous knowledge and western archaeological science for the benefit of both sides. The book gathers first the methodological diversity in the analysis of human tracks. Here major representatives of anthropological, statistical and traditional approaches feature the multi-layered methods available for the analysis of human tracks. Second it compiles case studies from around the globe of prehistoric human tracks. For the first time, the most important sites which have been found worldwide are published in a single publication. The third focus of this book is on firsthand experiences of researchers with indigenous tracking experts from around the globe, expounding on how archaeological sciencecan benefit from the ancestral knowledge. This book will be of interest to professional archaeologists, graduate students, ecologists, cultural anthropologists and laypeople, especially those focussing on hunting-gathering and pastoralist communities and who appreciate indigenous knowledge.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Footprints in caves with rock art.; Indigenous trackers from around the globe; Open Access; Pleistocene human footprints; Scientific value of prehistoric human footprints; Tracking in Caves

Reading Prehistoric Human Tracks: Methods & Material - Pastoors, Andreas; Lenssen-Erz, Tilman (Springer International Publishing, 2021)
This Open Access book explains that after long periods of prehistoric research in which the importance of the archaeological as well as the natural context of rock art has been constantly underestimated, research has now begun to take this context into focus for documentation, analysis, interpretation and understanding. Human footprints are prominent among the long-time under-researched features of the context in caves with rock art. In order to compensate for this neglect an innovative research program has been established several years ago that focuses on the merging of indigenous knowledge and western archaeological science for the benefit of both sides. The book gathers first the methodological diversity in the analysis of human tracks. Here major representatives of anthropological, statistical and traditional approaches feature the multi-layered methods available for the analysis of human tracks. Second it compiles case studies from around the globe of prehistoric human tracks. For the first time, the most important sites which have been found worldwide are published in a single publication. The third focus of this book is on firsthand experiences of researchers with indigenous tracking experts from around the globe, expounding on how archaeological sciencecan benefit from the ancestral knowledge. This book will be of interest to professional archaeologists, graduate students, ecologists, cultural anthropologists and laypeople, especially those focussing on hunting-gathering and pastoralist communities and who appreciate indigenous knowledge.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Footprints in caves with rock art.; Indigenous trackers from around the globe; Open Access; Pleistocene human footprints; Scientific value of prehistoric human footprints; Tracking in Caves

Reading spoor: Epistemic aspects of indigenous knowledge and its implications for the archaeology of prehistoric human traces - Lenssen-Erz, Tilman; Pastoors, Andreas (Reading Prehistoric Human Tracks, 2021)
The spoor of animals and humans alike contain rich information about an individual and about a momentary activity this individual performed. If the-arguably hard-wired-human ability to read spoor and tracks is sufficiently trained, a footprint allows to glean from it various physical, kinetic, medical, social and psychologic data about an individual, as has been observed among various populations across the globe. The Ju|'hoansi San from northern Namibia still today practice traditional hunting so that tracking is a skill that is required and trained on a daily base. For a good tracker, the information she or he gets from spoor is equally rich on animal and human footprints, and it is not necessary that the tracker has been exposed before to the individual whose spoor she/he reads. In order to allow an assessment of how tenable are the interpretations by contemporary hunter-gatherers of prehistoric human footprints, this chapter elucidates methodological aspects of tracking and situates this ability in an epistemological framework.
Created from Fastlane, Scopus look-up
Keywords: Abduction; Deduction; Hunter-gatherers; Hypothetico-deductive reasoning; Induction; Tacit knowledge; Tracking

Rohmaterial im Überfluss? - Pastoors, Andreas; Tafelmaier, Yvonne (Archäologie in Deutschland, 2020)

Site formation and chronology of the new Paleolithic site Sima de Las Palomas de Teba, southern Spain - Kehl, Martin; Burow, Christoph; Cantalejo, Pedro; Domínguez-Bella, Salvador; Durán, Juan José; Henselowsky, Felix; Klasen, Nicole; Linstädter, Jörg; Medianero, Javier; Pastoors, Andreas; Ramos, José; Reicherter, Klaus; et al. (Quaternary Research, 2016)
The newly identified Paleolithic site Sima de Las Palomas de Teba hosts an almost seven-m-thick sediment profile investigated here to elucidate the rock shelter's chronostratigraphy and formation processes. At its base, the sediment sequence contains rich archeological deposits recording intensive occupation by Neanderthals. Luminescence provides a terminus ante quem of 39.4 ± 2.6 ka or 44.9 ± 4.1 ka (OSL) and 51.4 ± 8.4 ka (TL). This occupation ended with a rockfall event followed by accumulation of archeologically sterile sediments. These were covered by sediments containing few Middle Paleolithic artifacts, which either indicate ephemeral occupation by Neanderthals or reworking as suggested by micromorphological features. Above this unit, scattered lithic artifacts of undiagnostic character may represent undefined Paleolithic occupations. Sediment burial ages between about 23.0 ± 1.5 ka (OSL) and 40.5 ± 3.4 ka (pIRIR) provide an Upper Paleolithic chronology for sediments deposited above the rockfall. Finally, a dung-bearing Holocene layer in the uppermost part of the sequence contains a fragment of a human mandible dated to 4032 ± 39 14C yr BP. Overall, the sequence represents an important new site for studying the end of Neanderthal occupation in southern Spain.
Created from Fastlane, Scopus look-up
Keywords: Luminescence dating; Micromorphology; Neanderthal occupation; Site formation processes

Spätpleistozäne Kunst in Inden-Altdorf, Rheinland - Pastoors, Andreas; Lenssen-Erz, Tilman (All der holden Hügel ist keiner mir fremd: Festschrift zum 65. Geburtstag von Claus-Joachim Kind, 2019)

Tagungsbericht des internationalen Workshops “The Upper-Late Palaeolithic Transition in Western Central Europe. Typology, Technology, Environment and Demography“ - Holzkämper, Jörg; Kretschmer, Inga; Maier, Andreas; Baales, Michael; von Berg, Alex; Bos, Johanna; Bradtmöller, Marcel; Edinborough, Kevan; Flohr, Stefan; Giemsch, Liane; Grimm, Sonja; Hilpert, Johanna; et al. (Archäologische Informationen, 2013)

The contribution of 3D visual technology to the study of Palaeolithic knapped stones based on refitting - Delpiano, Davide; Peresani, Marco; Pastoors, Andreas (Digital Applications in Archaeology and Cultural Heritage, 2017)
Lithic refitting studies can produce highly detailed data on knapping technologies and cores reduction strategies, human skills, natural and cultural formation processes, lithic economy, and intra-site land-use. However, lithic refitting analysis is notoriously time-consuming and can be tricky when the specimens must be handled in the search for refits; moreover, estimation of volumes, angles, convexities, cross-sections, and missing pieces can prove difficult. In our opinion, the 3D tool could be used in order to address these problems. We applied this approach to an archaeological sample, performing a multiple refitting analysis on a virtual support. This enabled better preservation of the original pieces, easier handling, a more complete interaction with the model, and finally, better exploration of the archaeological information, including the virtual reconstruction of the missing pieces. Moreover, thanks to the 3D support the ease with which these data can be disseminated negates the limitations caused by distance and subjectivity.
Created from Fastlane, Scopus look-up
Keywords: 3D visual technology; Discoid technology; Knapped stone; Neanderthal; Refitting

The Grotta di Cala dei Genovesi – new studies on the Ice Age cave art on Sicily - Tusa, Sebastiano; Di Maida, Gianpiero; Pastoors, Andreas; Piezonka, Henny; Weniger, Gerd-Christian; Terberger, Thomas (Praehistorische Zeitschrift, 2014)

The Investigation of the Ardales Cave, Spain – 3D Documentation, Topographic Analyses, and Lighting Simulations based on Terrestrial Laser Scanning - Hoffmeister, Dirk; Zellmann, Stefan; Pastoors, Andreas; Kehl, Martin; Cantalejo, Pedro; Ramos, José; Weniger, Gerd Christian; Bareth, Georg (Archaeological Prospection, 2016)
This contribution shows the application of terrestrial laser scanning in an integrative approach for the documentation and analyses of the Ardales Cave, southern Spain, which is in many respects an important geoarchaeological site. For the survey of the cave, a combination of the Riegl LMS Z420i laser scanner with a real-time kinematic global positioning system (RTK-GPS) from Topcon and further tachymetric measurements were used. The achieved three-dimensional (3D) model of the cave and the surrounding hill documents the current topography and dimensions of the cave. Additional geoarchaeological data were successfully integrated in a 3D geographical information system (GIS) database and high-resolution records of a structured-light scanner were combined with the 3D model of the cave. The 3D model is further used for the estimation of the ceiling thickness that reveals areas for additional entrances. Lighting simulations based on path tracing were conducted for the determination of areas that are reached by natural direct or indirect light. In this case, the weight and size of the instrument was a logistic constraint to reach certain areas and to achieve a complete model of the cave. Overall, the method is feasible for the documentation of this cave and the investigations based on the derived 3D models. Copyright © 2015 John Wiley & Sons, Ltd.
Created from Fastlane, Scopus look-up
Keywords: 3D GIS; 3D model; caves; geoarchaeology; LiDAR; lighting simulation

The Mäanderhöhle – Palaeolithic Cave Art in Bavaria? - Blumenröther, Julia; Bosinski, Gerhard; Gebelein, Dieter; Irlinger, Walter; Lenssen-Erz, Tilman; Maier, Andreas; Niggemann, Stefan; Pastoors, Andreas; Sommer, C. Sebastian; Steguweit, Leif; Uthmeier, Thorsten; Winterstein, Gerhard (Palaeolithic rock and cave art in Central Europe? Proceedings of the XIXe International Rock Art Conference „Symbols in the landscape. Rock art and its context“ in Cáceres, 2015, 2019)

The Mäanderhöhle. Palaeolithic cave art in Bavaria? - Pastoors, Andreas; Blumenröther, Julia; Bosinski, Gerhard (Palaeolithic rock and cave art in Central Europe?, 2018)

The repeated replacement model - Rapid climate change and population dynamics in Late Pleistocene Europe - Bradtmöller, Marcel; Pastoors, Andreas; Weninger, Bernhard; Weniger, Gerd-Christian (Quaternary international, 2012)

Tracking in Caves. Experience based reading of Pleistocene human footprints in French caves - Pastoors, Andreas; Lenssen-Erz, Tilman; Ciqae, Tsamkxao; Kxunta, Ui; Thao, Thui; Bégouën, Robert; Biesele, Megan; Clottes, Jean (Cambridge Archaeological Journal, 2015)

Tracking in Caves: Indigenous Ichnology - Pastoors, Andreas; Lenssen-Erz, Tilman (Encyclopedia of Global Archaeology, 2019)
In prehistoric research the importance of the archaeological as well as the natural context of rock art has been underestimated over long periods. Only recently has research begun to take this context into focus for documentation, analysis, interpretation, and understanding. Human footprints are most prominent among the long-time under-researched features of the context of cave art. In order to compensate for this neglect, a special research program has focused on the merging of indigenous knowledge and Western archaeological science for the benefit of both sides. With the expert assistance of indigenous San hunters from the Namibian Kalahari, this “Tracking in Caves” project endeavored to better understand aspects of the Upper Paleolithic human behavior, traces of which are preserved in footprints in painted caves in southern France. The three professional indigenous trackers were invited to Europe and conducted in-depth research in the caves Niaux, Pech Merle, Fontanet,...<br

Tuc d'Audoubert - Pastoors, Andreas; Bégouën, Robert (Bouquetins et Pyrénées: Inventaire des représentatioins du Paléolithique pyrénéen, 2022)

Tuc-d'Audoubert, grotte (Montesquieu-Avantès, Ariège, France) - Pastoors, Andreas; Bégouën, Robert (2021)

Überlegungen zur denkmalpflegerischen Evaluation von Oberflächenfundstellen aus dem Paläolithikum und Mesolithikum - Uthmeier, Thorsten; Pastoors, Andreas; Claßen, Erich; Weniger, Gerd-Christian (Das Ganze ist mehr als die Summe seiner Teile. Festschrift für Jürgen Kunow, 2019)

With the back to the art. Context of pleistocene cave art - Pastoors, Andreas; Lenssen-Erz, Tilman; Ontañón, Roberto; Weniger, Gerd-Christian (2017)

With the back to the art. Context of Pleistocene cave art - Pastoors, Andreas; Lenssen-Erz, Tilman; Ontañón, Roberto; Weniger, Gerd-Christian (Quaternary international, 2017)